2019
DOI: 10.1002/adma.201903904
|View full text |Cite
|
Sign up to set email alerts
|

Conformable Hybrid Systems for Implantable Bioelectronic Interfaces

Abstract: of Things (IoT) to wellness and medical technologies. In the past decade, significant efforts have been deployed to exploit these technologies to design and manufacture conformable bioelectronic interfaces.Mechanical compliance is a critical specification for the long-term integration of on-skin devices and implants with a biological host. The latter is largely composed of soft tissues, with Young's moduli E in the range from 100 Pa to 10 MPa (excluding bones and cartilage), [1] and sustains different physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 154 publications
(604 reference statements)
0
85
0
Order By: Relevance
“…To modulate these body responses that affect the in vivo functionality and longevity of implantable devices, several strategies have been reported [72][73][74], either passively via physicochemical features, or actively with molecules or matrix. These studies have essentially focused on the use of biocompatible material coatings, chemical surface modification of the device, conformable bioelectronics, steroidal and nonsteroidal anti-inflammatory drugs and angiogenic drugs [71,75].…”
Section: Implantable Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To modulate these body responses that affect the in vivo functionality and longevity of implantable devices, several strategies have been reported [72][73][74], either passively via physicochemical features, or actively with molecules or matrix. These studies have essentially focused on the use of biocompatible material coatings, chemical surface modification of the device, conformable bioelectronics, steroidal and nonsteroidal anti-inflammatory drugs and angiogenic drugs [71,75].…”
Section: Implantable Biosensorsmentioning
confidence: 99%
“…Conformable devices able to reduce the mechanical mismatches between the implant and the biological tissue have also been used as a strategy to overcome FBR in implantable biosensors [72]. For example, Wang et al [88] reported on functionalized multi-walled carbon nanotubes twisted into helical fiber bundles that mimic the hierarchical structure of muscle and allow the monitoring of multiple disease biomarkers in vivo.…”
Section: Bio-potential Sensorsmentioning
confidence: 99%
“…Requirements for encapsulation of flexible electronics can be more stringent than rigid counterparts, when close contact with human tissues occurs (on‐skin and implantable systems), liquid materials are enclosed (liquid metals, electrolytes, fluid for mechanical buffering [ 63 ] ), or harsh environmental conditions are commonplace during operation (building‐integrated devices, aerospace applications). From materials perspective, use of both conventional rigid encapsulation materials (e.g., SiN x , SiO x , SiC) and flexible polymeric encapsulation materials (e.g., polyimide, parylene‐C, silicones) [ 12,65 ] are necessary to harness the superior passivation properties of the former and mechanical flexibility and durability of the latter. Meanwhile, rational molecular design for new polymers with combined optimal properties should be explored [ 66 ] to overcome the current shortfall in barrier properties against moisture and other vapor molecules.…”
Section: The Thorny Path Of Lab‐to‐fab Translationmentioning
confidence: 99%
“…In addition, medical devices, especially implants, that incorporate flexible electronics although frequently reported in academic journals, are far from matured for real‐world application. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Block diagram of the implemented system showing the sensor array used for ion and moisture ingress experimentation and the measurement engine used for automatic control, readout, and transmission of the measurement results to off-chip for further processing. [27], [28] conformal coatings have been proposed which add minimally to the overall size and weight of the device and could make possible the realization of more flexible implants [29], [30], [31]. These protective coatings usually feature high barrier properties and aim at increasing the lifetime operation of the chip by blocking moisture and ions ingress.…”
Section: Introductionmentioning
confidence: 99%